(untitled) (LEARNing Landscapes, 2011)
In this interview, author and professor R. Keith Sawyer describes the importance of and interconnections among creativity, collaboration, and the science of learning. He explains that the older paradigm of schooling from 50 years ago where rote learning was predominant is no longer relevant in a knowledge-based society. We now have to prepare students for jobs that require adaptability, flexibility, and creativity. He endorses an approach to education that fosters a deeper conceptual understanding, especially through collaborative creativity. He maintains that true innovation usually comes from a collaboration of individuals rather than a single, brilliant insight. Finally, he comments on recent findings in cognitive neuroscience.